Preparation of a hollow fiber membrane made of antifouling PVDF/Zeolit using the dip-coating technique - Mumtazah, Zuhriah; Adinda Yufriza; Husna Wardati; Ditta Kharisma Yolanda Putri; Meta Fitri Rizkiana; Reva Edra Nugraha (Journal of Biobased Chemicals, 2023)
The practical technique for membrane modification is dip coating. This study coats a PVDF hollow fiber membrane-based composite with a coating of zeolite. The composite is made of a polyvinylidene fluoride (PVDF) membrane. During water filtering, the separation capabilities and propensities of composite membranes for organic impurities were examined. Fourier-transform infrared spectroscopy analysis of the findings demonstrated that the Zeolite coating was successfully deposited on the PVDF membrane. The flux recovery ratio increases from 69% to 80% while the relative flux drop decreases from 63% to 50%. A composite PVDF membrane dip-coating of Zeolite with a GA and H2SO4 ratio of 1:2 is needed to remove about 75% of humic compounds from effluent. The results of this study show that the addition of Zeolite with a GA and H2SO4 layer can greatly improve the hydrophilicity, selectivity, and anti-organic fouling of the PVDF hollow fiber membrane.